# How do you solve #-(3/4)x^2 + 2 = 0 #?

##### 1 Answer

Aug 21, 2015

#### Answer:

#### Explanation:

Start by isolating

#-3/4x^2 + color(red)(cancel(color(black)(2))) - color(red)(cancel(color(black)(2))) = -2#

#-3/4x^2 = -2#

then multiply both sides by

#(-4/3) * (-3/4)x^2 = -2 * (-4/3)#

#x^2 = 8/3#

To solve for

#sqrt(x^2) = sqrt(8/3)#

#x = +- (2sqrt(2))/sqrt(3)#

You can simplify this by rationalizing the denominator

#x = +- (2sqrt(2) * sqrt(3))/(sqrt(3) * sqrt(3)) = color(green)(+- (2sqrt(6))/3)#